Enhancement in Cane Productivity through Rleay Intercropping of Autumn Sugarcane with skipped row tansplanted rice - SINGH, S. N.; SAH, A. K.; SINGH, P. R.; SINGH, I.; SINGH, R. K.; DULLU, DULLU (Indian Farming, 2015)
In rice-sugarcane growing areas of the Indian sub-tropics, sugarcane planting in autumn season (October) is not practically feasible due to delayed harvesting of low land rice (specially scented varieties) and fields remaining wet. In such agroecosystems, autumn planting of sugarcane as a relay intercrop with rice in September-end can conveniently be adopted to improve the overall productivity and profitability of the cropping system. The system may be worth adopting by sugarcane farmers as it saves not only time and energy on pre-planting tillage operations but also ensures higher productivity and better economic returns.